ANALISIS PENGARUH CAR, NPL, LDR, BOPO, DPK DAN SIZE TERHADAP KINERJA PERBANKAN DI INDONESIA (Studi Pada Perbankan Konvensional yang Terdaftar di BEI Periode 2014-2018) - Serafina, Dea Oktivani; Sampurno, R. Djoko (Diponegoro Journal of Management, 2020)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Operational Costs Operating Income (BOPO), Third Party Funds (DPK), and Company Size (SIZE) on banking performance proxied by Return on Assets (ROA). The population in this study is conventional commercial banks in Indonesia which are listed on the Indonesia Stock Exchange (IDX) for the period 2014 - 2018. The number of samples in this study were 23 banks, where the sample collection uses a purposive sampling method. The analysis technique used is multiple linear regression analysis and first performs the classic assumption test, the F statistical test, and the t statistical test. The results of hypothesis testing in this study indicate that CAR, DPK, and SIZE have significant positive effect on ROA, then NPL and BOPO have a significant negative effect on ROA, whereas LDR does not significantly influence ROA. Based on the results of the study showed that the BOPO variable had the greatest effect on ROA. The result of the R Square value is 0.820, so that 82% of the ROA variable can be explained by the CAR, NPL, LDR, BOPO, DPK, and SIZE variables, while the remaining 18% is explained by other factors not explained in this study.